A study on isolated DCM converter for high efficiency and high power factor. - Dong-Kurl Kwak (Journal of electrical engineering & technology)
This paper is studied on a novel buck-boost isolated converter for high efficiency and high power factor. The switching devices in the proposed converter are operated by soft switching technique using a new quasi-resonant circuit, and are driven with discontinuous conduction mode (DCM) according to pulse width modulation (PWM). The quasi-resonant circuit makes use of a step up-down inductor and a loss-less snubber capacitor. The proposed converter with DCM also simplifies the requirement of control circuit and reduces a number of control components. The input ac current wave form in the proposed converter becomes sinosoidal waveform in proportion to the magnitude of input ac voltage under constant switching frequency. As a result, it is obtained by the proposed converter that the switching power losses are low, the efficiency of the converter is high, and the input power factor is nearly unity. The validity of analytical results is confirmed by some simulation results on computer and experimental results.